2019
DOI: 10.1187/cbe.18-12-0248
|View full text |Cite
|
Sign up to set email alerts
|

Online and Clicker Quizzing on Jargon Terms Enhances Definition-Focused but Not Conceptually Focused Biology Exam Performance

Abstract: Mastery of jargon terms is an important part of student learning in biology and other science, technology, engineering, and mathematics domains. In two experiments, we investigated whether prelecture quizzes enhance memory for jargon terms, and whether that enhanced familiarity can facilitate learning of related concepts that are encountered during subsequent lectures and readings. Undergraduate students enrolled in neuroanatomy and physiology courses completed 10-minute low-stakes quizzes with feedback on jar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

5
4

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 39 publications
1
11
0
Order By: Relevance
“…In line with other studies (e.g. Mayer et al, 2009;Pan et al, 2019), the teachers taught both conditions identically:…”
Section: The Interventionsupporting
confidence: 82%
“…In line with other studies (e.g. Mayer et al, 2009;Pan et al, 2019), the teachers taught both conditions identically:…”
Section: The Interventionsupporting
confidence: 82%
“…It may also suggest that Bloom's taxonomy may not be as hierarchical as originally proposed (Anderson et al, 2001;Krathwohl, 2002). In a recent study (Pan et al, 2019), a lack of a connection was shown: researchers found that, even explicit testing on low-level terminology that resulted in a clear testing effect did not lead to an increase in conceptual learning on higher-level items. Alternatively, it is also possible that Bloom's is hierarchical but without explicit testing, the testing effect fails to come through.…”
Section: Discussionmentioning
confidence: 93%
“…, 2001 ; Krathwohl, 2002 ). In a recent study ( Pan et al. , 2019 ), a lack of a connection was shown: researchers found that, even explicit testing on low-level terminology that resulted in a clear testing effect did not lead to an increase in conceptual learning on higher-level items.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis by Rowland (2014; see also Adesope et al, 2017) found that the typical effect size of that improvement, which is also known as the testing effect , is g = 0.50, 95% CI [0.42, 0.58]. Testing effects have been successfully demonstrated across a considerable range of materials (Rawson & Dunlosky, 2011), in a variety of authentic educational settings (e.g., McDaniel et al, 2011; Pan, Cooke, et al, 2019), and when posttesting is implemented in a variety of test formats (Rowland, 2014). Further, a meta-analysis by Pan and Rickard (2018) found that the typical size of a transfer effect following posttesting (that is, the ability to apply learning to new contexts, such as to solve application and inference questions, or to recall information on a criterial test that uses a different format) is d = 0.40, 95% CI [0.31, 0.50].…”
Section: Posttesting: Retrieval Practice Improves Learningmentioning
confidence: 99%